2009
DOI: 10.1136/hrt.2008.155770
|View full text |Cite
|
Sign up to set email alerts
|

Remote ischaemic preconditioning reduces myocardial injury in patients undergoing cardiac surgery with cold-blood cardioplegia: a randomised controlled trial

Abstract: Background: Remote ischaemic preconditioning (RIPC) induced by brief ischaemia and reperfusion of the arm reduces myocardial injury in coronary artery bypass (CABG) surgery patients receiving predominantly crossclamp fibrillation for myocardial protection. However, coldblood cardioplegia is the more commonly used method world wide. Objective: To assess whether RIPC is cardioprotective in CABG patients receiving cold-blood cardioplegia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
142
1
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 207 publications
(150 citation statements)
references
References 33 publications
4
142
1
1
Order By: Relevance
“…Subgroup analysis of the studies reporting outcomes of CABG with or without AVR showed results consistent with the general trend (SMD -0.42; 95% CI: -0.70 to -0.13, p = 0.005) and I 2 = 67% [9,[20][21][22][23][24][25][26][27]. Studies concerning isolated valvular surgery did not confirm the protective result of rIPC; however, heterogeneity (I 2 = 94%) was essentially influencing the outcome effect under the random [28][29][30].…”
Section: Sensitivity Analysismentioning
confidence: 58%
See 3 more Smart Citations
“…Subgroup analysis of the studies reporting outcomes of CABG with or without AVR showed results consistent with the general trend (SMD -0.42; 95% CI: -0.70 to -0.13, p = 0.005) and I 2 = 67% [9,[20][21][22][23][24][25][26][27]. Studies concerning isolated valvular surgery did not confirm the protective result of rIPC; however, heterogeneity (I 2 = 94%) was essentially influencing the outcome effect under the random [28][29][30].…”
Section: Sensitivity Analysismentioning
confidence: 58%
“…This correction changed the heterogeneity from 83% to 0% and the effect was still highly significant (SMD -0.69; 95% CI: -0.86 to -0.51; p = 0.00001). With regard to studies scoring > 5 points on the Jadad scale, the meta-analysis showed a significant reduction of necrosis markers, although the effect was smaller than the effect for the whole population (SMD -0.40; 95% CI: -0.69 to -0.11; p = 0.005) [9,20,21,[23][24][25][26]30]. We analyzed the effect of rIPC on diabetic patients separately, and compared it with trials in which Remote ischemic preconditioning versus standard myocardial protection in cardiac surgery: ten years of clinical trials.…”
Section: Experimental Cardiovascular and Lung Researchmentioning
confidence: 99%
See 2 more Smart Citations
“…Mid-scale clinical studies have shown that RIC applied prior to CABG [39,81] and PCI [38] reduces surrogate markers of myocardial injury, but until recently, the clinical relevance of these findings was questionable. However, two recent publications strongly suggest, that RIC should find a place as standard adjunctive therapy in elective PCI and CABG.…”
Section: Remote Ischemic Conditioning In Predictable Ischemiamentioning
confidence: 99%